2023
DOI: 10.1021/acsbiomaterials.2c01097
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Porous Magnesium Alloy Scaffolds Promote the Repair of Osteoporotic Bone Defects in Rats through Activating the Wnt/β-Catenin Signaling Pathway

Abstract: In this study, biomimetic porous magnesium alloy scaffolds were prepared to repair femoral bone defects in ovariectomized osteoporotic rats. The purpose of the study was to investigate the effect of biomimetic porous magnesium alloy scaffolds on repairing osteoporotic bone defects and possible mechanisms. The animal model of osteoporosis was established in female SD rats. Three months later, a bone defect of 3 mm in diameter and 3 mm in depth was created in the lateral condyle of the right femur. The rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Bioceramics are brittle and difficult to process into an ideal shape, limiting their use in making fusion cages . Due to the advantages of magnesium (Mg) alloy, such as good biocompatibility, mechanical properties close to human bone, and good osteogenic induction, the development of Mg-based orthopedic implants has received widespread attention in recent years. , Studies on applying Mg-based implants in extremity bone have shown that the implants work well in promoting osteogenesis. …”
Section: Introductionmentioning
confidence: 99%
“…Bioceramics are brittle and difficult to process into an ideal shape, limiting their use in making fusion cages . Due to the advantages of magnesium (Mg) alloy, such as good biocompatibility, mechanical properties close to human bone, and good osteogenic induction, the development of Mg-based orthopedic implants has received widespread attention in recent years. , Studies on applying Mg-based implants in extremity bone have shown that the implants work well in promoting osteogenesis. …”
Section: Introductionmentioning
confidence: 99%